Animal remains from 17th century Carnide, Lisbon, Portugal - Detry, Cleia (2020)
Excavations undertaken in 2012 by the Centro de Arqueologia de Lisboa (CAL), in Largo do Coreto (Bandstand square) in Carnide (Lisbon, Portugal), uncovered over 7,000 faunal remains. These came from 60 underground pits previously used for storage, especially cereal, and subsequently, between 1550 and 1660 AD, filled with domestic rubbish. Most remains belonged to mammals and birds, with a significant number of molluscs. They are presumably food waste which therefore tell us something about the way of life of the inhabitants of 17th century Carnide. These people clearly depended primarily on domestic animals such as cattle, pig, sheep and goat as well as chicken and goose. Large wild animal remains were strikingly absent though there were some bones of small game like rabbit and partridge. For the rabbit it is unclear if it was the domestic or wild variety. A few remains of ferret and raptors point to their possible uses for hunting. A number of whole skeletons of cats and dogs, with no trace of butchery, were probably deposited as garbage.